2016
DOI: 10.1080/09168451.2015.1107466
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate levels control HT22 murine hippocampal cell death by regulating biphasic patterns of Erk1/2 activation: role of metabolic glutamate receptor 5

Abstract: Extracellular glutamate concentration is a critical determinant of neuronal cell fate. We recently demonstrated that HT22 murine hippocampal cell viability was reduced by exposure to high concentrations of glutamate, whereas low concentrations promoted cell survival. Extracellular signal-regulated kinase (Erk)1/2 activation by glutamate is important for both glutamate-induced cell death and survival. In this study, we investigated the role of glutamate-induced or hydrogen peroxide (H2O2)-induced Erk1/2 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Moreover, Erk1/2 phosphorylation was markedly reduced following B355227 co-exposure, suggesting an apoptotic role of Erk1/2. Consistent with the results of previous studies, the present study reported that the levels of p-Erk1/2 were increased following glutamate treatment in HT22 cells, leading to cell death (18,49,50). Following treatment with B355227, the phosphorylation of Erk1/2 decreased, leading to an increase in the levels of cell survival.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, Erk1/2 phosphorylation was markedly reduced following B355227 co-exposure, suggesting an apoptotic role of Erk1/2. Consistent with the results of previous studies, the present study reported that the levels of p-Erk1/2 were increased following glutamate treatment in HT22 cells, leading to cell death (18,49,50). Following treatment with B355227, the phosphorylation of Erk1/2 decreased, leading to an increase in the levels of cell survival.…”
Section: Discussionsupporting
confidence: 92%
“…ROS plays a central role in glutamate-mediated oxidative stress and displays a synergistic association with Erk1/2 (47). However, in ischemia, Erk1/2 plays key roles in both the survival and apoptosis of cells, depending on the time and concentration of glutamate exposure (48,49). In the present study, an increase in the levels of Erk1/2 phosphorylation was revealed following 24 h glutamate exposure.…”
Section: Discussionsupporting
confidence: 49%
“…14 Accordingly, numerous studies have shown that Glutamate administration to neuronal and nonneuronal cells induces a rapid increase in ERK1/2 and Akt phosphorylation. [51][52][53][54] It is known that both ERK and Akt pathways regulate multiple biological functions including gene expression and cell cycle 55,56 and that, in the testis, they play a crucial role in spermatogonia proliferation. [57][58][59][60][61] In line with these results, we found an increase of PCNA and Aurora B protein expression in lysated NMDA-and L-Glu-treated GC-1cells.…”
Section: Eaas Increase Glua1 and Glua2/3 Protein Expressions In Gc-1 ...mentioning
confidence: 99%
“…14 The extracellular signal-regulated kinases (ERKs) 1 and 2 (1/2) promote cell growth and differentiation; moreover, oxidative stress induces the sustained phosphorylation of ERKs 1/2. 15 Furthermore, c-Jun N terminal kinase (JNK) and p38 have been shown to modulate cell differentiation and death by cytokines, ultraviolet light, heat shock, and a variety of other factors. 16 Therefore, the identication of antioxidants that can weaken the level of glutamate-induced apoptosis is a good strategy for the prevention and treatment of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%